Dryden, the public writer, 1660-1685 - McFadden, George, 1916-2006 (Princeton legacy library., 1978)
This reinterpretation of Dryden's life and works shows how his writings were influenced by important contemporaries, the power struggles of Restoration politics, and the friendships and rivalries of society. Professor McFadden sees Dryden's poems, plays, and essays as forms of address immediately related to the historical moment and the patron or dedicatee. This approach created a dialogue between the writer and his age that enabled him to interpret some of the deepest and still inchoate social and political attitudes of his day. The author traces Dryden's rise to notoriety, along with the development of the poetic techniques he used to acquire and form his audience. Dryden's work for the theater figures prominently in the analysis, including the prologues, epilogues, and especially the dedications, which have never before been exploited. Historical and biographical findings lead Professor McFadden to new readings of major works, lie also draws important conclusions bearing upon the genre of the heroic play, the relationships between lampoon, satire, and comedy in Restoration writing, and the sense in which the term "Augustan" may be applied to that writing. Finally, he demonstrates that Dryden was a writer in the fullest contemporary sense of the word: a worker in language, carrying on a creative exchange with the contingencies and forms of his time. Originally published in 1978. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905